Anthropometric and performance comparisons in professional baseball players - Hoffman, J.; Vazquez, J.; Pichardo, N. (The Journal of Strength and Conditioning Research, 2010)
To compare anthropometric and athletic performance variables across the different levels of professional baseball and to examine the relationship that these variables have on baseball specific power performance. 343 professional baseball players over a two year period were assessed for height, weight, body composition, grip strength (GRIP), vertical jump peak (VJPP) and mean (VJMP) power, 10 yd sprint speed, agility (pro agility test), and 30-sec cone jump. Subject population consisted of players on the rosters of one of the minor league affiliates (rookie [R], A, AA, AAA) or on the major league roster (MLB). All testing occurred at the beginning of spring training in each of the seasons studied. Data from both years of testing was combined. One-way analysis of variance was utilized to compare anthropometric and performance variables between levels of play and correlation analysis was used to examine the relationships between performance variables and baseball specific power performance (e.g., homeruns [HR] total bases [TB], slugging pct [SLG%], and stolen bases [SB]). MLB were significantly heavier than players in AA, A and R. Players in AAA were significantly heavier than players in A and R. Players in R and A had significantly lower body fat% than players in MLB and AAA. However, players in R had significantly lower lean body mass than MLB, AAA, and AA. Grip strength in MLB and AAA were significantly greater than A and R. Players in MLB were significantly faster than players in AA, A and R. Significant differences were seen in VJPP and VJMP between MLB and players in AA, A and R. Players in AAA and AA demonstrated greater power (p < 0.05) than players in A and R. Correlation analyses revealed significant bivariate correlations between VJPP and HR (r = 0.48), TB (r = 0.28) and SLG% (r = 0.47) and between VJMP and HR (r = 0.48), TB (r = 0.27) and SLG% (r = 0.47). Significant bivariate correlations were also seen between GRIP and HR (r = 0.32), TB (r = 0.21) and SLG% (r = 0.27). A significant inverse correlation was seen between 10 yd sprint and SB (r = -0.42). Results indicate that both anthropometric and performance variables are able to differentiate professional baseball players at different levels of competition. Speed, lower body power and grip strength also significantly correlated with baseball specific performance variables. Focus on strength, power and speed improvements in baseball players appears to be highly desirable in the development of their training program. The use of performance testing in player selection, especially in regards to the amateur draft, may potentially provide valuable information to general managers and scouting professionals in making a more educated decision in the signing and drafting of perspective professional baseball players.